THE STUDY OF WATER QUALITY FOR DEVELOPING TOURISM IN PARANGTRITIS COASTAL AREA, INDONESIA - Murtianto, Hendro; Lin, Shyang Woei; Chen, and Zue-er (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The quality of groundwater can be affected by natural and human factors condition; such as: litology, climate, time, and the activities of living beings, including humans as waste disposal industry, household waste, agricultural waste and the use of pesticides. The quality of groundwater can be determined by measuring physical, bological and chemical factors. The purposes of this issue are: (1) measuring the distribution of water quality in open aquifer; (2) groundwater potential for tourism purposes. This research took 9 water samples with purposive random sampling methods and geomorphological based analysis. Water analysis standart based on government regulation on Yogyakarta, Indonesia number 214/KPTS/1991. Groundwater in this area is still have huge standarized of clean water with classified as bicarbonate water, because the water flown through the limestone geologic materials. The evaluation of groundwater quality was performed by comparing the physical and chemical elements. Data collected in the field and the measurements in the laboratory. Physical data collected such as: electrical conductivity (EC), pH, color, taste, smell, and turbidity. Chemical data focus on major elements, such as: Ca2+, Mg2+, Na+, K+, Cl-, SO42, HCO3-, and CO3-. Groundwater in Parangtritis still has good quality of groundwater, so it can be developed for the purpose of consumption needs and clean water supply. But, people have to aware that using groundwater on coastal area can increase saltwater intrusion.